Effectiveness of Carvedilol versus Indapamide in Uncontrolled Diabetic Hypertensive Patients being Treated with Olmesartan and Amlodipine - Hasan, Md Masud; Hossain, AKM Mosharrof; Ahmad, Hussain; Munni, Hashina; Kashem, Fatema Binte; Chowdhury, Md Abu Nayeem; Rahman, KM Hafizur (Medicine Today, 2018)
Hypertension is the commonest preventable cause of death among the diabetic patient. Current guidelines recommend using combination drug therapy in case of uncontrolled hypertension in diabetic patient. Even though, duel combinations are sometimes insufficient to achieve target blood pressure. Objective of this study was to evaluate the efficacy and safety of Indapamide and Carvedilol as third drug in controlling hypertension in diabetic patients. This prospective comparative study was conducted in 32 well controlled diabetic patient with uncontrolled hypertension those who taking Olmesartan (20 mg/day) and Amlodipine (5 mg/day). Addition of both the drugs showed significant reduction of all the blood pressure parameters at the end of six weeks therapy without any major adverse effects. Systolic blood pressure decreased from 169.71±9.26 to 119.41±12.48 in Indapamide group (p<0.001) and 167.67±12.94 to 122.67±18.79 in Carvedilol group (p<0.001). Diastolic blood pressure decreased from 98.23±7.06 to 76.76±8.65 in Indapamide group (p<0.001) and 94.67±11.41 to 79.33±10.83 in Carvedilol group (p<0.001). Mean arterial pressure also reduced from 122.06±5.35 to 90.98±8.72 in Indapamide group (p<0.001) and 119.00±10.61 to 93.78±12.51 in Carvedilol group (p<0.001). Only ten patients suffered from mild adverse effects, such as epigastric discomfort, nausea, light headedness and drowsiness; which did not required stopping the therapy. Both the drugs are found to be equally effective as well as safe as third drug along with Olmesartan and Amlodipine in controlling hypertension in well controlled diabetic patients. Medicine Today 2018 Vol.30(1): 5-10